The Moral Mappings of South and North - Wagner, Peter (2017)
What is the 'Global South' and where is it? The term 'Global South' marks a new attempt at providing order and meaning in the current global political constellation, replacing the term 'Third World'. But the term 'Global South' is fraught with many ambiguities. This book explores the possible meanings of this new distinction and assesses the advantages and disadvantages of adopting it for understanding the contemporary world. It casts a wide exploratory net, looking at how the way that we interpret the world has changed over time.